(untitled) (Revista Electrónica REDINE, 2018)
The University as a knowledge generating institution has developed optimal management tools for academic competitiveness and to satisfy the environment, which demands qualified professionals to face the disagreements of business dynamics. The Coordination of Professional Practices of DAC-UCLA provides the labor market with interns capable of solving problems immersed in business dynamics, for which it is necessary to control their management, for which the University Internship Regulations were approved as a mechanism; in this sense, the need arose to carry out this study to know the link between this legal framework and the management processes. This research was conducted during the academic period 2009-2 and 2011-1. It was a qualitative approach work, non experimental level, descriptive and documentary type, a formal interview was used as a collection instrument. The relevance of this research was to achieve a strategic diagnosis where the lack of a long-term management philosophy was concluded, since the management is characterized by being proactive, with team culture, in addition to a value system based on beliefs. The components of the regulations are legally established, although the structure of the Coordination is not formally established as a unit of the DAC, and the control processes are developed in an incipient manner. The study of strategic and management control allowed to make recommendations such as developing a strategic planning for the unit, formalization of organizational manuals, functions, positions and procedures as well as control mechanisms and the approval of the coordination as a functional unit of the DAC.